William Shakespeare's The force doth awaken : Star Wars part the seventh - Doescher, Ian (Quirk Books, 2017)
A retelling of The Force awakens in iambic pentameter, the style of Shakespeare. To BB-8 or not to BB-8? That is the question! Star-crossed lovers reunite, a lost knight is found, and tragedy befalls the house of Solo.